EKSPLOITASI ALAM DALAM NOVEL ORANG-ORANG PROYEK KARYA AHMAD TOHARI - Putri, Evelita Destiia; Dewi, Novita; Nugraha, Setya Tri (Universitas Negeri Makassar, 2024)
This research aims to describe the factors that cause behavior and the impact of natural exploitation in the novel Orang-Orang Proyek by Ahmad Tohari. The method used in this research is library research. This research uses ecocritical theory with an environmental ethics study model to analyze the causal factors and impacts of nature exploitation. The data is in the form of sentence quotations contained in the novel Orang-Orang Proyek. The data source comes from the novel Orang-Orang Proyek. Data were collected through reading and note-taking techniques. The results showed that the two main factors causing the exploitation of nature in the novel are economics and power. These factors have violated six moral principles towards environmental wisdom. The impact of natural exploitation contained in this novel is pollution and damage to natural ecosystems, disruption of educators' livelihoods.